African Literature in Translation: Towards Adopting a Minor Translation Theory - Bethlehem Attfield (Media and Intercultural Communication: A Multidisciplinary Journal)
Building on a comparative literary analysis of two translated African short stories, this article examines whether culture-specific metaphors and symbolisms effectively enrich the texture of a translated text or detract the reader from following the narration. Then, it takes into account critical reception of such culture-loaded stories, for developing an effective translation theoretical framework. Considering that the source texts are written in Arabic and Amharic, both Semitic languages with long literary traditions, the article particularly sets out to adopt a translation approach that focuses on power and means to keep their literary and cultural integrity. The decision to adopt Deleuze and Guattari’s minor literature as a basis for translation theory is highly influenced by Reta’s, the Amharic author’s Hitsinawinet narrative theory. The maze-like framework that Hitsinawinet uses is inspired by the concept of ‘rhizome’ to effectively map out the complex and fragmented history of Ethiopia. The first draft of the Amharic translation is done based on a translation framework formulated by adopting the concept of rhizome as a map. This concept enables constant modifications, incorporating readers’ views through focus group discussions. These complementary methods can facilitate a broader, more dynamic depiction that does not undermine the integrity of the source text.